Zakat as Alternative Source of State Revenue: Comparative Study of Indonesia and Malaysia from Legal Perspective - Agatha Jumiati; Esti Aryani; Kesya Zhalibina Sunarto (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This research analyzes the legal status of zakat within the state financial system and explores its potential integration as a sharia-based fiscal instrument in Indonesia through a comparative study with Malaysia. In Islamic law, zakat functions both as a religious obligation and as a mechanism for wealth redistribution aimed at achieving social justice. However, under Indonesia’s positive law framework, zakat is still treated as a socio-religious institution outside the formal state fiscal system, as stipulated in Law Number 23 of 2011 on Zakat Management. In contrast, Malaysia has successfully integrated zakat into its Islamic fiscal policy through the authority of the State Islamic Religious Council (MAIN), which holds legal legitimacy as a regional public body. This study adopts a normative and comparative legal approach by examining statutory regulations, Islamic legal doctrines, and zakat institutional practices in both countries. The findings indicate that the integration of zakat into Indonesia’s fiscal system is constitutionally permissible and does not conflict with Article 23A and Article 34 paragraph (1) of the 1945 Constitution, as it aligns with welfare state principles and the state’s responsibility toward poverty alleviation. The legal implications of such integration include the establishment of lex specialis regulating zakat as a sharia fiscal instrument, harmonization with state finance laws, and the strengthening of institutional legitimacy and accountability in zakat management. Therefore, zakat holds significant potential to become a core pillar of Islamic economic law that supports economic equity and enhances national fiscal resilience.